Divergent profiles of rhizosphere soil carbon and nitrogen cycling in Pinus massoniana provenances with different types of carbon storage - Huang, Zichen; Wang, Jiannan; He, Xin; Zhang, Mengyang; Ren, Xingyue; Yu, Wenya; Yao, Sheng; Ji, Kongshu (Frontiers in Microbiology, 2025)
IntroductionIn subtropical China, P. massoniana is a timber tree species which have a great potential for carbon sequestration. However, few studies have investigated how varying levels of carbon storage in P. massoniana provenances affect the soil microbial functional potential related to nutrient cycling within the rhizosphere.MethodsIn this investigation, metagenomic sequencing was employed to explore the differences in carbon and nitrogen cycling capabilities among rhizosphere microbial communities within P. massoniana provenances, categorized by high, medium, and low levels of carbon storage.ResultsOur findings revealed a significant increase in the relative abundance of Acidobacteriota and Ascomycota by 23 and 61%, respectively, whereas Basidiomycota significantly decreased by 8% in the rhizosphere of P. massoniana provenances with high carbon storage compared with those with low carbon storage. The variability in carbon storage among P. massoniana provenances was linked to marked disparities in the presence of key genes essential for carbon and nitrogen cycling within their rhizosphere soils.DiscussionNotably, in P. massoniana provenances characterized by high carbon storage, the rhizosphere presented a significantly elevated presence of genes associated with carbon decomposition, carbon assimilation, methane generation, and denitrification, in stark contrast to provenances with medium and low carbon storage. Furthermore, P. massoniana provenances with high carbon storage rates presented increased transformation and availability of soil carbon and nitrogen, along with increased potential for ecological restoration. Moreover, the rhizosphere soil nitrification of P. massoniana provenances with low carbon storage surpassed that of other provenances, leading to increased available nitrogen content and elevated nitrate leaching risk. In the P. massoniana rhizosphere, critical soil factors, including soil organic carbon (SOC), total nitrogen (TN), pH, and nitrate nitrogen (NO3−-N) content, significantly shape the functionality of genes associated with carbon and nitrogen cycling. In conclusion, our study lays a scientific foundation for establishing P. massoniana plantations and identifying P. massoniana provenances with superior ecological value and potential.